Mythology in Sulalatus Salatin Manuscript - Rizki Dwi Andina; Laila Rohani; Abdi Mubarak Syam (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This research delves into the Sulalatus Salatin manuscript, exploring its historical context and content to identify and describe the myths embedded within, reflecting the Malay society around the 15th century. The study aims to deepen the understanding of the Sulalatus Salatin manuscript and the prevalent myths of that era. Utilizing the historical method, the research encompasses three stages: identifying the research problem, collecting data, and analyzing content through a textology approach to comprehend past societal views on mythology. Data collection involves library research to find relevant studies, skimming the text to examine each chapter, and documenting various sources such as documents, notes, and archives. The results reveal that the Sulalatus Salatin manuscript narrates the reigns of the Malay Sultanate of Malacca, depicting Malay values such as philosophy, ethics, leadership, aesthetics, language, and religion. The manuscript records events related to the rise, glory, and downfall of the Malay Kingdom of Malacca in 1511 CE, highlighting the introduction of Islam and Malacca's role as a center of Islamic education.